2019
DOI: 10.3389/fnins.2019.01309
|View full text |Cite
|
Sign up to set email alerts
|

Anticholinergic Drugs in Geriatric Psychopharmacology

Abstract: Drugs with anticholinergic action are widely prescribed in the elderly population due to their potential clinical benefits. However, these benefits are limited by adverse effects which may be serious in particular circumstances. This review presents different aspects of the use of anticholinergics in old age with a focus in psychogeriatric patients. We critically review published data on benefits and disadvantages of anticholinergics, which are often controversial. Prevalence, pathophysiology and measurement m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
93
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(114 citation statements)
references
References 137 publications
(216 reference statements)
2
93
0
9
Order By: Relevance
“…It is widely acknowledged that anticholinergic medications have a detrimental impact on cognitive performance (Richardson et al, 2018;López-Álvarez et al, 2019). Due to increasing health complications in later life, the use of polypharmacy in elderly people is high, and many commonly prescribed drugs have anticholinergic effects, including neuropsychiatric drugs (eg tricyclic antidepressants, antipsychotic agents, antiepileptic drugs, antiparkinsonian medication) and a range of non-psychoactive drugs (eg antihistamines, antispasmodics, antiulcer agents, bronchodilators, diuretics, corticoids, cardiovascular medications) (López-Álvarez et al, 2019).…”
Section: Medicalmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely acknowledged that anticholinergic medications have a detrimental impact on cognitive performance (Richardson et al, 2018;López-Álvarez et al, 2019). Due to increasing health complications in later life, the use of polypharmacy in elderly people is high, and many commonly prescribed drugs have anticholinergic effects, including neuropsychiatric drugs (eg tricyclic antidepressants, antipsychotic agents, antiepileptic drugs, antiparkinsonian medication) and a range of non-psychoactive drugs (eg antihistamines, antispasmodics, antiulcer agents, bronchodilators, diuretics, corticoids, cardiovascular medications) (López-Álvarez et al, 2019).…”
Section: Medicalmentioning
confidence: 99%
“…It is widely acknowledged that anticholinergic medications have a detrimental impact on cognitive performance (Richardson et al, 2018;López-Álvarez et al, 2019). Due to increasing health complications in later life, the use of polypharmacy in elderly people is high, and many commonly prescribed drugs have anticholinergic effects, including neuropsychiatric drugs (eg tricyclic antidepressants, antipsychotic agents, antiepileptic drugs, antiparkinsonian medication) and a range of non-psychoactive drugs (eg antihistamines, antispasmodics, antiulcer agents, bronchodilators, diuretics, corticoids, cardiovascular medications) (López-Álvarez et al, 2019). A UK case-control study conducted in over 40 000 patients with dementia aged 65-99 years and approximately 284 000 control subjects without dementia found that dementia was associated with an increasing average anticholinergic cognitive burden (ACB) score, and a strong association between some classes of anticholinergic drugs (eg antidepressants, urological agents, and antiparkinsonian drugs) and future dementia incidence (Richardson et al, 2018).…”
Section: Medicalmentioning
confidence: 99%
“…Table 1 highlights the different kinds of commonly used drugs with AC effects. However, despite their therapeutic benefits in a variety of diseases, AC drugs are also known to have many side effects as they are capable of binding to other targets in the body (Lopez-Alvarez et al, 2019). Besides, most AC drugs are lipophilic which allows them to cross the blood-brain barrier (BBB) such as the firstgeneration antihistamine and anti-depressant to exert their effects in the brain (Chancellor et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…These properties of the AC drugs might have led to their adverse effects on the central nervous system which include cognitive decline and neurodegenerative diseases (Lopez-Alvarez et al, 2019). The AC effects of drugs can be categorized into two main events: the peripheral and the central events (Barkin and Stein, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The inhibition of acetylcholine seems to be connected with the occurrence of many side effects on the peripheral nervous system (e.g., urinary retention, constipation, tachycardia) and the central nervous system. Furthermore, it is always important to consider that older persons are particularly at risk of adverse drug reactions, mainly because of (1) the often present polypharmacy, and (2) modifications in pharmacokinetics and pharmacodynamics occurring with aging [1].…”
mentioning
confidence: 99%